2022
DOI: 10.29244/jam.10.1.33-45
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor yang Memengaruhi Ketahanan UMKM Makanan dan Minuman Bersertifikat Halal saat Pandemi COVID-19 di Kota Banda Aceh

Abstract: The existence of the COVID-19 pandemic has implications for the global economic sector, including in Indonesia. The decline in economic performance is not only felt by large multinational and national companies, but also by MSME players. This research aims to examine the factors of resilience of MSMEs during the COVID-19 pandemic, so that the results of this research can be a survival strategy for MSMEs, especially during the pandemic. The research data was collected through an interview process with 100 food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
0
0
1
Order By: Relevance
“…The motivation to increase profits in the long term in obtaining certification is proven by several studies such as Fotopoulos et al,(2009); Escanciano et al (2014). Similar results were stated by Fajriani & Wiliasih (2018). Their research concluded that three factors influence the interest of MSEs in Bogor Regency towards halal certification, one of which was the impact of certification which was expected to increase profit.…”
Section: The Influence Of Internal Factors On the Mses Interest To Ha...supporting
confidence: 63%
See 1 more Smart Citation
“…The motivation to increase profits in the long term in obtaining certification is proven by several studies such as Fotopoulos et al,(2009); Escanciano et al (2014). Similar results were stated by Fajriani & Wiliasih (2018). Their research concluded that three factors influence the interest of MSEs in Bogor Regency towards halal certification, one of which was the impact of certification which was expected to increase profit.…”
Section: The Influence Of Internal Factors On the Mses Interest To Ha...supporting
confidence: 63%
“…Several studies on halal has been previously done. Fajriani & Wiliasih (2018) analyzed the characteristics of MSEs in Bogor Regency and analyzed the factors that influenced MSEs to participate in regular halal certification. The results show that three factors influence the interest of MSEs in Bogor Regency for halal certification, namely: the impact of halal certification on profit, level of owner's education and access to halal certification.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, the use of digital marketing has become an alternative for developing marketing strategies in various business sectors, including BUMDes convection (Rahmayanie et al, 2022). In the context of MSMEs, Muhammad Bangun S, Ritha F Dalimunthe, Endang Sulistya Rini, Yeni Absah -29-digitalization also plays an important role in increasing business resilience, performance and business growth (Maulana & Yuliani, 2023;Hardi et al, 2022;Viariani et al, 2022). However, research results show that digitalization is not a moderating variable that strengthens or weakens the influence of company assets or organizational legitimacy on banking financial performance (Supriatin & Aulia, 2022).…”
Section: Digitalizationmentioning
confidence: 99%
“…Oleh karena itu dapat disimpulkan bahwa sangat penting bagi penerus usaha untuk memperhatikan kinerja mereka guna menunjang ketahanan usahanya. Hasil ini konsisten penelitian terdahulu yang dilakukan oleh (Viariani et al, 2022) bahwa ketahanan usaha berpengaruh positif terhadap kineja bisnis. b. Pengaruh Karakter Wirausaha terhadap Kinerja Bisnis: Hasil pengujian menunjukan koefisien jalur (β) 0,10 dan bernilai positif serta p-value 0,001, yang artinya karakter wirausaha mempunyai pengaruh positif terhadap kinerja bisnis.…”
Section: Gambar 4 Pengaruh Mediasiunclassified